Semiconductor Power Devices Physics, Characteristics, Reliability - Lutz, Josef (Springer International Publishing, 2018)
This book discusses semiconductor properties, pn-junctions and the physical phenomena for understanding power devices in depth. Working principles of state-of-the-art power diodes, thyristors, MOSFETs and IGBTs are explained in detail, as well as key aspects of semiconductor device production technology. Special peculiarities of devices from the ascending semiconductor materials SiC and GaN are discussed. This book presents significant improvements compared to its first edition. It includes chapters on packaging and reliability. The chapter on semiconductor technology is written in a more in-depth way by considering 2D- and high concentration effects. The chapter on IGBTs is extended by new technologies and evaluation of its potential. An extended theory of cosmic ray failures is presented. The range of certain important physical relationships, doubted in recent papers for use in device simulation, is cleared and substantiated in this second edition.